Can High-Quality Jobs Help Workers Learn New Tricks? A Multi-Disciplinary Review of Work Design For Cognition - Parker, Sharon; Ward, M.K.; Fisher, Gwen (Taylor & Francis, 2021)
Understanding whether and how work design affects human cognition is important because: (1) cognition is necessary for job performance, (2) digital technologies increase the need for cognition, and (3) it is vital to maintain cognitive functioning in the mature workforce. We synthesize research from work design, human factors, learning, occupational health, and lifespan perspectives. Defining cognition in terms of both knowledge and cognitive processes/fluid abilities, we show that five types of work characteristics (job complexity, job autonomy, relational work design, job feedback, and psychosocial demands) affect employees’ cognition via multiple pathways. In the short-to-medium term, we identify three cognitively-enriching pathways (opportunity for use of cognition, accelerated knowledge acquisition, motivated exploratory learning) and two cognitively-harmful pathways (strain-impaired cognition, depleted cognitive capacity). We also identify three longer-term pathways: cognitive preservation, accumulated knowledge, and ill-health impairment). Based on the emerging evidence for the role of work design in promoting cognition, we propose an integrative model suggesting that short-to-medium term processes between work design and cognition accumulate to affect longer-term cognitive outcomes, such as the prevention of cognitive decline as one ages. We also identify further directions for research and methodological improvements.